আমি নারী : তিনশ বছরের (১৮-২০শতক) বাঙালি নারীর ইতিহাস - বেগম, মালেকা; হক, সৈয়দ আজিজুল (ঢাকা : ইউনিভার্সিটি প্রেস লিমিটেড, 2001)
Social conditions and status of Bengali women from 18th to 20th century, with special reference to feminism.
গ্রন্থপঞ্জী (পৃষ্ঠা [২১৬]-২১৯) ও নির্ঘণ্ট অন্তর্ভুক্ত।
BIED
Complimentary copy from BIED
In Bengali.
Keywords: Women, Bengali -- India -- Bengal -- Social conditions; Women, Bengali -- India -- West Bengal -- Social conditions; Women, Bengali -- Bangladesh -- Social conditions; Feminism -- India -- Bengal -- History; Feminism -- India -- West Bengal -- History; Feminism -- Bangladesh -- History